Modelagem e simulação computacional de transformadores de potência para estudo de transitórios em altas frequências - Wickert, Humberto Margel (2016)
This paper presents a proposed the modeling of power transformers for high-frequency electromagnetic transients. The application of this model allows the evaluation of the windings behavior against the voltage surges imposed by the electric power system. Besides the model, the required calculations to determine the concentrated and distributed parameters which define the representative circuit are detailed. The calculations were performed for a 25 MVA power transformer, using the data obtained from a technical audit between both client and manufacturer, known as design review. The representation of the equipment for the simulation is realized through a descriptive language, known as netlist. The impossibility of measuring the voltage along the power transformer windings subjected to voltage surges has motivated the development of the proposed model and computer simulation. Aiming to evaluate the potentialities of the developed model, the simulations for the power transformer were performed focusing on the determination of the lightning impulse transient voltage distribution along the windings and fully evaluating the obtained results. Alterations of the studied transformer s project were also addressed, considering the windings traditionally used by the manufacturers. A qualitative comparison between the responses of both power transformers is also presented.